2010
DOI: 10.1177/000313481007601206
|View full text |Cite
|
Sign up to set email alerts
|

Transcardiac Bullet Embolus to the Pulmonary Vein

Abstract: Letters to the Editor should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 3 double-spaced pages excluding an Abstract and sub-headings with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The authors stated that the use of 2D echocardiogram intraoperatively may have led to finding the bullet in the left atrium before it migrated in a retrograde fashion to the right pulmonary vein. 13 , 14 TEE intraoperatively is the modality of choice for confirming intracardiac missile emboli, with TEE preferred to transthoracic echocardiogram since TEE helps better visualize the level of myocardial damage. 15 In addition, echocardiogram sometimes demonstrates how deeply embedded the foreign body is, further affecting medical decision making.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors stated that the use of 2D echocardiogram intraoperatively may have led to finding the bullet in the left atrium before it migrated in a retrograde fashion to the right pulmonary vein. 13 , 14 TEE intraoperatively is the modality of choice for confirming intracardiac missile emboli, with TEE preferred to transthoracic echocardiogram since TEE helps better visualize the level of myocardial damage. 15 In addition, echocardiogram sometimes demonstrates how deeply embedded the foreign body is, further affecting medical decision making.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…As mentioned earlier, Schulman et al reported one case in which a right pulmonary vein embolus caused fatal outflow obstruction between the right lung and left heart. 13 While most emboli to the left heart presumably originate from the pulmonary veins, and some left-heart missiles may be managed conservatively, missile emboli retained in the pulmonary veins are dangerous. Though future case reports may give us better understanding of this phenomenon, as it stands now, all missile emboli in the pulmonary veins likely require removal ( Figure 5 ).…”
Section: Managementmentioning
confidence: 99%